2016
DOI: 10.1021/acscatal.6b01962
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Addition of Indoles to Activated N-Benzylpyridinium Salts: Nucleophilic Dearomatization of Pyridines with Unusual C-4 Regioselectivity

Abstract: The catalytic enantioselective dearomatization of pyridines with nucleophiles represents a direct and convenient access to highly valuable dihydropyridines. Available methods, mostly based on N-acylpyridinium salts, give addition to the C-2/C-6 of the pyridine nucleus, rendering 1,2-/1,6-dihydropyridines. Herein, we present an alternative approach to this type of dearomatization reaction, employing activated N-benzylpyridinium salts in combination with a bifunctional organic catalyst. Optically active 1,4-dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Finally, some experimental investigations led us to propose a reaction pathway showing the catalyst involved in the double (covalent and H-bond) activation of both of the reaction partners. In 2016, our group disclosed the first example of organocatalytic enantioselective dearomatization of N-alkylpyridinium salts [60]. Overcoming the poor reactivity (and dearomatized product instability) by placing an EWG group (such as nitro or cyano) at the 3-position, thus enhancing the electrophilicity of the cation, we were able to productively engage N-alkylpyridinium salts in nucleophilic dearomatizations, using indoles as reaction partners (Scheme 20).…”
Section: N-alkylpyridinium Saltsmentioning
confidence: 99%
“…Finally, some experimental investigations led us to propose a reaction pathway showing the catalyst involved in the double (covalent and H-bond) activation of both of the reaction partners. In 2016, our group disclosed the first example of organocatalytic enantioselective dearomatization of N-alkylpyridinium salts [60]. Overcoming the poor reactivity (and dearomatized product instability) by placing an EWG group (such as nitro or cyano) at the 3-position, thus enhancing the electrophilicity of the cation, we were able to productively engage N-alkylpyridinium salts in nucleophilic dearomatizations, using indoles as reaction partners (Scheme 20).…”
Section: N-alkylpyridinium Saltsmentioning
confidence: 99%
“…In organic chemistry, they serve as ionic liquids 5 (2) and phase transfer catalysts 6 , exhibit a diverse range of biological activities (3,4) (Figure 1a), and have a long history as synthetic intermediates, an area that has seen a recent surge of new advancements. Representative of their versatile reactivity, pyridinium and related salts can undergo full or partial reductions [7][8][9] , cycloadditions 10,11 , photochemical isomerizations 12 , cross couplings 13 , addition of one-or two-electron heteroatom or carbon nucleophiles 8,14 , and facile C-H metalations 15 , and many of these include asymmetric variants [16][17][18] (Figure 1b). The breadth of available transformations make pyridinium salts valuable templates for accessing functionalized 6-membered aza-heterocyclic scaffolds, which are prevalent in agrochemicals, alkaloid natural products, and are the most commonly encountered heterocyclic motif in FDA approved small molecule drugs 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, the organocatalysts were introduced to more demanding N-alkylpyridinium salts, which provided an alternative platform with opportunities in the enantioselective dearomatization of pyridine compared with the N-acyl analogues (Scheme 1b). [5] A regioselectivity issue arises from the two different positions prone to nucleophilic attack present on the pyridine nucleus. This results in either a variable C2/C6 or C4 selectivity depending on the substitution pattern at the pyridine ring.…”
Section: Introductionmentioning
confidence: 99%
“…Only the reactions involving the C4 nucleophilic sites were observed preferentially in organocatalytic dearomatization reactions. [5] To the best of our knowledge, the origin of the regioselectivity of these kinds of reactions is still unclear. Our previous studies demonstrated that the reactivity of the active sites strongly influences regioselectivity.…”
Section: Introductionmentioning
confidence: 99%